Tolerance of high-yielding corn hybrids to drought stress during the early growth stage - Jiovana Kamila Vilas-Boas; Fábio Steiner; Alan Mario Zuffo; Jorge González Aguilera; Charline Zaratin Alves (Revista Ciência Agronômica)
ABSTRACT The early seedling stage is one of the most vulnerable and critical growth stages in the plant life cycle and determines the final plant stand and yield. Corn hybrids have distinct degrees of drought tolerance, and exploiting this characteristic is important to enhance agricultural production in many tropical regions of the world. Fourteen corn hybrids commonly grown in the central-western region of Brazil, in Cassilândia, Mato Grosso do Sul, were assessed for drought tolerance during the early plant growth stage. Plants were grown in the Plant Ecophysiology Laboratory under non-stressful (control) and stressful (moderate drought) conditions for 28 days. Drought stress was induced with an -0.30 MPa iso-osmotic solution prepared with polyethylene glycol (PEG-6000). The emergence rate, seedling length, and seedling dry matter were measured, and then drought tolerance indexes were calculated. Our results showed that root length is an important morphological trait for plant adaptation to drought stress conditions. Therefore, plant breeding programs should select corn genotypes with longer roots to develop commercial hybrids with superior performance under limited soil water availability. The corn hybrids FS 575 PWU, GNZ 7757 VIP3, LG 36745 PRO4, and MG 545 PWU have greater tolerance to drought stress and are the most suitable genotypes to be grown in conditions of low soil water availability. The AG 8088 PRO2 corn hybrid has greater susceptibility to drought stress and should not be recommended for cultivation in conditions of reduced soil water availability.